2020
DOI: 10.1177/0308022620941396
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functions of children with brain tumor in the treatment process

Abstract: Introduction This study assesses the cognitive functions of children with brain tumor, including orientation, spatial perception, praxis, visuomotor constructions and thinking operations. The aim of the study was to assess the cognitive functions of children with brain tumor in the treatment process and the effects of different treatments on cognitive functionality. Method Cognitive functions of children with brain tumor ( n = 102) and children with typical development ( n = 90) were assessed with the Dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Studies have indicated that children with a history of brain tumor have a high risk of cognitive disability, particularly in terms of processing speed, executive functions, memorization, and focus. 10,12,[51][52][53][54] This influences their cognitive function, and results in poor occupational performance. 12 Most studies have explored the correlation between neurocognition assessments and the cognitive abilities of patients with CBT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have indicated that children with a history of brain tumor have a high risk of cognitive disability, particularly in terms of processing speed, executive functions, memorization, and focus. 10,12,[51][52][53][54] This influences their cognitive function, and results in poor occupational performance. 12 Most studies have explored the correlation between neurocognition assessments and the cognitive abilities of patients with CBT.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,[51][52][53][54] This influences their cognitive function, and results in poor occupational performance. 12 Most studies have explored the correlation between neurocognition assessments and the cognitive abilities of patients with CBT. Few have explored whether damage to a tumor site or pharmacotherapy affect quality of life and functional performance for patients with CBT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiotherapy is considered the primary cause of neurological complications and neurocognitive decline in children with cancer (Mabbott et al, 2005). In this respect, it is clearly stated in the literature that children with a brain tumour and leukaemia diagnosis, which are frequently seen in childhood and treated with intense radiation therapy, have neurocognitive deficits (Mavrea et al, 2021; Önal & Huri, 2021).…”
Section: Introductionmentioning
confidence: 99%